Mobilizing a Community–Academic Partnership to Provide DIY Handwashing Stations to Skid Row Residents During COVID-19. Issue 1 (January 2021) - DiGuiseppi, Graham; Corcoran, Callahan; Cunningham, Todd; Nguyen, Hoan; Noel, Monique; White, Pete; Bar, François
The coronavirus (COVID-19) pandemic is having a devastating impact on global health. In the United States and abroad, there is concern for how the novel coronavirus will affect vulnerable populations, including people experiencing homelessness. Individuals who lack stable housing are more likely to have preexisting health conditions and limited access to basic preventative hygiene practices such as handwashing and sanitizing. The situation has become critical in Los Angeles' Skid Row neighborhood, where nearly 5, 000 unhoused residents (13% of the city's homeless population) reside on any given night. Community members' concerns have mounted as social and health services in the area have decreased, and early efforts to prevent the transmission of coronavirus did not adequately address the lack of access to handwashing stations and hand sanitizing products. This Practice Note details an academic–community partnership that uses grassroots organizing to provide "do-it-yourself" handwashing stations to the Skid Row neighborhood. We describe how an academic–community partnership was mobilized to establish innovative practices in response to the coronavirus, offering lessons and recommendations for others hoping to do similar work.